Caracterização das raças de H. maydis e comportamento de linhagens de milho frente à raça T - de Paulo Campos, Vicente; de Carvalho, Murilo Geraldo (Revista Ceres, 2025)
Five Helminthosporium maydis isolates out of 7 collected in the States of Espírito Santo, Minas Gerais, Paraná, and Rio Grande do Sul, Brazil, have been characterized as race T under the criteria of (1) symptoms induced on susceptible and resis tant varieties, (2) sporulation repression in infected leaf discs, and (3) inhibition of root elongation by culture extracts. The other two isolates were characterized as race O.